The Influence of Referral Marketing and Customer Trust on Purchasing Decisions Through Customer Satisfaction at PT. Dharma Lautan Utama Surabaya - Kartika, Chandra; Dandy, Firman; Soenarmi, Soenarmi (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This research is entitled